Papers of Percival Conrad Mowle - Mowle, P. C. (Percival Conrad), 1872-1951. (1824)
Various typescripts and manuscripts of "History of the Australian Customs Service", "Settlement in Australia", "Port regulations and orders", "The origin of Customs" as well as correspondence, photographs (including daguerreotypes), and printed material.
Manuscript reference no.: MS 7650.
National Library of Australia Manuscript Section at MS 258 and MS 7649.
Genealogist and writer, Mowle was the compiler of the first four editions of A genealogical history of pioneer families in Australia, an attempt at identifying the early families and their descendants, 1788-1838 excluding convicts. See also Pioneer families of Australia, of the above work, p.125.
Descriptive list available.
Keywords: Mowle, P. C. -- 1872-1951 -- Archives; Australian Customs Service -- History; Customs administration -- Australia -- History; Public officers -- Archives; Public servants